Disciples of a Saint Engineer (The Buchen of Spiti) (Bodhi Path, 2020)
Spiti is home to some of the oldest Buddhist monasteries in the Himalayan region. For instance, Tabo monastery, kee monastery, Tangyud monastery, Gungri monasteries are some of the main monasteries of great importance in Spiti valley. It is strong hold of the last of the Buchen1 tradition in Pin valley and those great and very ancient monasteries which played very important roles in maintaining the culture and religious identity of the Spiti valley. Buchen tradition originated into Spiti from Tibet. Initially when Thang sTong rGyalpo founded Buchen tradition in Tibet, its influence was so pervasive that it spread all over the Himalayan regions in Inida. But today, all has changed and Buchen tradition has more or less disappeared, except in the remote Pin valley in Spiti. Currenty there is a community of people continuing their unique Buchen traditions. Buchen are class of people who uses entertainment to spread the teachings of the Buddha. They call themselves the great son of Thang sTong rGyalpo who founded Buchen tradition in Tibetin the 14th century. Buchen tradition played a very important role in the preservation of religion and is of profound cultural importance to Spiti valley as a whole.
Keywords: Saint Engineer; Buchen of Spiti